ARE FINANCIAL PERFORMANCE AND CORPORATE SOCIAL RESPONSIBILITY DETERMINANTS TO FIRM VALUE? - Dimas Isaac; Temy Setiawan (INQUISITIVE : International Journal of Economic, 2022)
This study aims to empirically prove the influence of capital structure, profitability, and corporate social responsibility on firm value. There are 3 independent variables used in this study, namely capital structure as measured by the Debt to Equity Ratio (DER), profitability as measured by Return on Assets (ROA), and corporate social responsibility as measured by the Corporate Social Responsibility Disclosure Index ( CSRDI) with content analysis technique. The population used in this study uses manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in the period 2018 to 2020. Data collection was carried out using a purposive sampling technique with a total sample of 20 companies. The analytical method used is multiple linear regression analysis with SPSS version 26. 0 applications and a significant value of 5%. The results of this study are the capital structure variable has a significant positive effect on firm value, the profitability variable has a significant positive effect on firm value, and the corporate social responsibility variable has no effect on firm value.